Respect for Human Dignity in Caring for Patients with Cancer in Ilam, Perspectives of Patients and Nurses - Borji, Milad; Mousavi Moghadam, Seyyed Rahmatollah; Meymizade, Mehdi (Asian Pacific Journal of Cancer Biology, 2016)
Objectives: Human dignity is one of the most important characteristics and ethical concerns in nursing care. This study was conducted with the aim of evaluating respect for human dignity in care for patients with cancer from both patients’ and nurses' perspectives. Methods: In this cross-sectional descriptive study, 150 patients with cancer and 150 healthcare nurses were selected through convenience sampling. Data was collected from patients and nurses using a human dignity questionnaire about patient care; the validity and reliability of the questionnaire had been confirmed by previous studies. Data analysis was done using SPSS 20 software to carry out a statistical-descriptive test (mean and standard deviation) and statistical-inferential tests (t-test and one-way ANOVA). Results: According to the findings, for both patients and nurses, human dignity is very important in care for patients with cancer. Results also indicated that nurses consider respect for human dignity in patients with cancer to be at a desirable level, while from patients' perspective, it is low. Conclusions: Due to patients’ feeling that respect for human dignity is low in care for patients with cancer, it is necessary to implement appropriate nursing interventions to increase human dignity in care for patients with cancer.